The Employment Effect of Reforming a Public Employment Agency - Andrey Launov; Klaus Wälde (Center for Economic Studies and ifo Institute (CESifo), 2015)
By how much does an increase in operating effectiveness of a public employment agency (PEA) and a reduction of unemployment benefits reduce unemployment? Using a recent labour market reform in Germany as background, we find that an enhanced effectiveness of the PEA explains about 20% of the observed post-reform unemployment decline. The role of unemployment benefit reduction explains just about 5% of the observed decline. Due to disincentive effects resulting from the reform, the reform of the PEA could have had an even higher impact on unemployment reduction if there had been less focus on long-term unemployed workers.
Keywords: E24; J65; J68; 330; employment agencies; unemployment benefits; labour market reform; unemployment; structural model